Spatially explicit risk assessment of marine megafauna vulnerability to Indian Ocean tuna fisheries. Issue 5 (24th May 2022) - Roberson, Leslie; Wilcox, Chris; Boussarie, Germain; Dugan, Emma; Garilao, Cristina; Gonzalez, Kristofer; Green, Madeline; Kark, Salit; Kaschner, Kristin; Klein, Carissa J.; Rousseau, Yannick; Vallentyne, Dan; et al.
Abstract: By‐catch is the most significant direct threat marine megafauna face at the global scale. However, the magnitude and spatial patterns of megafauna by‐catch are still poorly understood, especially in regions with very limited monitoring and expanding fisheries. The Indian Ocean is a globally important region for megafauna biodiversity and for tuna fisheries, but has limited by‐catch data. Anecdotal and scattered information indicates high by‐catch could be a major threat. Here, we adapt a Productivity Susceptibility Analysis tool designed for data‐poor contexts to present the first spatially explicit estimates of by‐catch risk of sea turtles, elasmobranchs, and cetaceans in the three major tuna fishing gears (purse seines, longlines, and drift gill nets). Our assessment highlights a potential opportunity for multi‐taxa conservation benefits by concentrating management efforts in particular coastal regions. Most coastal waters in the northern Indian Ocean, including countries that have had a minimal engagement with regional management bodies, stand out as high risk for fisheries interactions. In addition to species known to occur in tuna gears, we find high vulnerability to multiple gear types for many poorly known elasmobranchs that do not fall under any existing conservation and management measures. Our results indicate that current by‐catch mitigation measures, which focus on safe‐release practices, are unlikely to adequately reduce the substantial cumulative fishing impacts on vulnerable species. Preventative solutions that reduce interactions with non‐target species (such as closed areas or seasons, or modifications to gear and fishing tactics) are crucial for alleviating risks to megafauna from fisheries.